2018
DOI: 10.1158/0008-5472.can-18-0327
|View full text |Cite
|
Sign up to set email alerts
|

LRRC15 Is a Novel Mesenchymal Protein and Stromal Target for Antibody–Drug Conjugates

Abstract: Progress in understanding tumor stromal biology has been constrained in part because cancer-associated fibroblasts (CAF) are a heterogeneous population with limited cell-type-specific protein markers. Using RNA expression profiling, we identified the membrane protein leucine-rich repeat containing 15 (LRRC15) as highly expressed in multiple solid tumor indications with limited normal tissue expression. LRRC15 was expressed on stromal fibroblasts in many solid tumors (e.g., breast, head and neck, lung, pancreat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
163
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(175 citation statements)
references
References 43 publications
6
163
0
Order By: Relevance
“…Our study demonstrated that blocking LRRC15 expression may decrease both tumorigenicity and metastatic dissemination. This finding suggests that the LRRC15 protein may be a potential candidate as an antitumor target, a concept given further support by ongoing development of ABBV085 [41] an LRRC15-antibodytargeted drug conjugate.…”
Section: Discussionmentioning
confidence: 89%
“…Our study demonstrated that blocking LRRC15 expression may decrease both tumorigenicity and metastatic dissemination. This finding suggests that the LRRC15 protein may be a potential candidate as an antitumor target, a concept given further support by ongoing development of ABBV085 [41] an LRRC15-antibodytargeted drug conjugate.…”
Section: Discussionmentioning
confidence: 89%
“…LRRC15 was found to be highly expressed on the cell surface of stromal fibroblasts in many solid tumors. Additionally, LRRC15 was considered as a new marker of cancer-associated fibroblasts and cancers of mesenchymal origin and might be applicated in antibody-drug conjugate targeting the tumor stroma [22].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the biology of CAFs, including their origins, specific markers, functions, and clinical relevance, has gained increasing research interest in recent years (3)(4)(5)(6)(7)(8). Clinical trials of therapeutics that target CAFs are also emerging, with investigations on the underlying mechanisms (4,8,19,20).…”
Section: Introductionmentioning
confidence: 99%